STUDY OF UTILIZATION AND DEVELOPMENT OF TANGKAHAN FACILITIES SELAMAT DATANG TELUK NIBUNG DISTRICT TANJUNGBALAI CITY NORTH SUMATERA PROVINCE - Anggi Fitralaila Nasution; Syaifuddin Syaifuddin; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACKThis research was conducted in January 2019 in Tanjungbalai City, Teluk Nibung District, North Sumatera Province, to determine the type, size, condition and level of utilization and the possibility of developing existing facilities in Tangkahan Selamat Datang. The survey is carried out by direct observation to the field and interviews with fishermen, ship owners, and other parties related to this research. All data obtained is processed with a qualitative analysis, namely the System Approach. Based on the show analysisthat the facilities available at Tangkahan Selamat Datang are all very utilized, but some need development to facilitate the activities that are in the Tangkahan Selamat Datang. Facilities that need development include: construction of docks, the existence of facilities and infrastructure in Tangkahan, repairs to Tangkahan, the presence of shipyards. Keywords: Tangkahan, Utilization Level, Development